THERE IS MORE TO MANGROVES THAN JUST BEING SWAMPS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, May 2017 Unlike the beaches of Penang, the mangrove area is less visited or accessible to the public, let alone understood as an ecosystem that actually yields higher productivity than the sandy coastlines.